Co-delivery of doxorubicin and hydroxychloroquine via chitosan/alginate nanoparticles for blocking autophagy and enhancing chemotherapy in breast cancer therapy - Zhang, Hui; Xue, Qingwen; Zhou, Zihan; He, Ningning; Li, Shangyong; Zhao, Cheng (Frontiers in Pharmacology, 2023)
Breast cancer (BC) is the most common malignancy in women worldwide, and the standard treatment is chemotherapy or radiotherapy after surgery. In order to reduce the side effects of chemotherapy, various nanoparticles (NPs) have been discovered and synthesized, which has become a promising treatment for BC. In this study, a co-delivery nanodelivery drug system (Co-NDDS) was designed and synthesized with 2,3-dimercaptosuccinic acid (DMSA) coated Fe3O4 NPs as core encapsulated into chitosan/alginate nanoparticles (CANPs) shell, doxorubicin (DOX) and hydroxychloroquine (HCQ) as loading drugs. Smaller NPs carrying DOX (FeAC-DOX NPs) were loaded into larger NPs containing HCQ (FeAC-DOX@PC-HCQ NPs) by ionic gelation and emulsifying solvent volatilization methods. The physicochemical properties of this Co-NDDS were characterised, followed by in vitro studies of the anticancer effects and mechanisms using two different BC cell lines, MCF-7 cells and MDA-MB-231 cells. The results indicated that the Co-NDDS showcases exemplary physicochemical qualities and encapsulation capacity, facilitating accurate intracellular release through pH-sensitive attributes. Importantly, NPs can significantly increase the in vitro cytotoxicity of co-administered drugs and effectively inhibit the autophagy level of tumour cells. The Co-NDDS constructed in this study provides a promising strategy for the treatment of BC.